Oral Structural Breakdown and Sensory Perception of Plant-Based Emulsions - Arancibia-Aguilar, C; Riquelme-Hinojosa, N; Paredes-Toledo, J (Elsevier B.V., 2024)
Emulsion-based matrices correspond to an interesting structure for designing healthy and plant-based foods since they can simulate the texture of traditional foods, protect lipids from oxidation, and carry bioactive compounds. However, oral processing could modify their structure, affecting their sensory performance. So, it is necessary to understand the changes that occur during food consumption and their relationship with sensory perception. For that purpose, this research aimed to study the effect of droplet size and thickener type of plant-based emulsions on their structural breakdown under oral conditions and their sensory perception. Four oil-in-water (O/W) emulsions with different droplet sizes (nanoemulsions and conventional emulsions) and thickener types (starch and xanthan gum) were prepared. In vitro oral structural breakdown of emulsions was characterized using a rheological approach (saliva + sharing). The samples were later subjected to a sensory evaluation of aroma, flavor, consistency, and creaminess intensity by multiple paired comparison test (n = 50). Results showed different oral breakdown patterns due to droplet size and thickener type. Xanthan gum matrices were less susceptible to structure breakdown than starch-based matrices, particularly those with microscale droplet size (emulsions), due mainly to salivary α-amylase activity. Regarding sensory perception, xanthan gum-based matrices were perceived to have a higher consistency (nanoemulsion) and creaminess (conventional emulsion) than starch-based ones. Meanwhile, starch-based samples showed higher flavor (nanoemulsion) and aroma intensities (conventional emulsion). Therefore, the sensory characteristics of plant-based emulsions can be modulated by thickener type and droplet size. For example, xanthan gum-based nanoemulsions can increase the perceived consistency, while starch-based emulsions can increase the perceived flavor intensity. © 2024